Cloning, characterization of two female-specific AFLP markers and development of PCR-based sex identification method for the half-smooth tongue sole Cynoglossus semilaevis - Hongyu MA, Songlin CHEN, Jing LI, Jin-Zhen BI, Tianjun XU (Current Zoology, 2009)
Two female-specific AFLP (amplified fragment length polymorphism) markers (named CseF464 and CseF136) were isolated by using one selective primer combination (E-AGC/M-CTG) from the genomic DNA of 20 females and 20 males of the half-smooth tongue sole Cynoglossus semilaevis. Both the markers were re-amplified, recovered from the agarose gels, cloned and sequenced. Bioinformatics analysis indicated that the length of the two markers were 468bp and 134bp, respectively, and the sequences showed no similarity to each other, as well as to the known sequences deposited in the GenBank database using BLASTn. Two pairs of SCAR (sequence characterized amplified regions) primers were designed based on the sequences of the two female-specific markers. Furthermore, PCR-based genetic sex identification method was developed in Cynoglossus semilaevis. A specific fragment was amplified in all females but not in any males by using these SCAR primers on the initial 20 female and 20 male individuals of Cynoglossus semilaevis. The feasibility of the two SCAR primer pairs was confirmed in additional 100 individuals (50 females and 50 males). This allowed for reliable, rapid molecular identification of genetic sex of the species, genetic mapping on the sex chromosomes and better understanding of the sex determination and sex differentiation in the half-smooth tongue sole [Current Zoology 55 (4): 309–314, 2009].